Clinical features and the prognostic significance of ocular sarcoidosis - Halil Yanardag; Cuneyt Tetikkurt; Muammer Bilir; Halit Pazarlı (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2018)
The main objective of this study was to evaluate the clinical features of ocular sarcoidosis. The second aim was to assess the influence of eye involvement on the prognostic outcome, extrapulmonary organ, and endobronchial involvement in sarcoidosis patients. Third objective was to determine the contribution of ocular involvement to final diagnosis in patients presenting with an equivocal sarcoidosis diagnosis due to single organ disease. One hundred seventy two sarcoidosis patients paticipated in the study and were classified into two groups according to the existence of eye involvement. The patients were evaluated retrospectively in regard to clinical features, prognostic outcome, extensity of extrapulmonary organ, and endobronchial involvement between the two groups. Eighty patients (46.5%) had eye sarcoidosis. Ocular involvement was the initial symptom in 15 subjects (18.7%) while asymptomatic ocular sarcoidosis was observed in 14 patients (17.5%) at initial admission. Red eye was the most common symptom occuring in 26 patients (32.8%) while anterior uveitis was the most frequent site (38.4%) of involvement. The other relevant ocular structures in the order of decreasing frequency were posterior uvea, papilla, lacrimal gland, and sclera. Patients with ocular sarcoidosis had a worse prognosis and a more extensive extrapulmonary organ involvement than the patients without eye disease. Although endobronchial involvement was more common in these patients, it was not statistically significant. In 12 patients (15%) with an equivocal sarcoidosis, identification of eye involvement confirmed the final diagnosis. The results of our study reveal that the identification of ocular sarcoidosis appears to be a useful decisive clinical marker for determining the prognostic outcome of sarcoidosis patients. The incidence of extrapulmonary organ involvement was significantly higher in patients with ocular sarcoidosis. Detection of ocular disease was also useful for the final diagnosis in patients with a single organ sarcoidosis manifesting an indecisive clinical presentation. Recognition of ocular sarcoidosis is a rewarding and a preliminary clinical utility in sarcoidosis both for diagnosis and disease outcome while this finding may be an evidence of endobronchial involvement.